Lethal and Inhibitory Activities of Plant-Derived Essential Oils Against Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) Biotype B in Tomato - Fanela, T. L.M. [UNESP]; Baldin, E. L.L. [UNESP]; Pannuti, L. E.R. [UNESP]; Cruz, P. L. [UNESP]; Crotti, A. E.M.; Takeara, R.; Kato, M. J. (Springer Nature, 2016)
The silverleaf whitefly Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) is one of the most severe tomato pests in the world. The damage caused by this insect may compromise up to 100% of crop production, and management of this pest has relied on spraying of synthetic insecticides. However, due to the environmental issues associated with this practice, alternative methods such as the use of botanical pesticides are now used as a strategy of integrated pest management (IPM). We evaluated the effects of essential oils of five plant species on B. tabaci biotype B in tomato and demonstrate that the essential oils (0.5%) of Piper callosum (PC-EO), Adenocalymma alliaceum (AA-EO), Pelargonium graveolens (PG-EO), and Plectranthus neochilus (PN-EO) inhibit the settlement and oviposition of B. tabaci biotype B adults in tomato plants. In fumigation tests, A. alliaceum (AA-EO) at 0.4 μL/L of air after 72 h and 0.1 μL/L of air after 6 h was the most effective against nymphs and adults of B. tabaci biotype B, respectively. The major chemical constituents of PC-EO were identified as being safrole (29.3%), α-pinene (19.2%), and β-pinene (14.3%), whereas diallyl trisulfide (66.9%) and diallyl disulfide (23.3%) were the major compounds identified in AA-EO. This is the first report on the reduction of oviposition by the use of P. callosum (PC-EO) and A. alliaceum (AA-EO). In addition, the fumigant effect of A. alliaceum (AA-EO) on nymphs and adults has also been reported here for the first time.
Keywords: Botanical insecticides; fumigation; silverleaf whitefly; Solanum lycopersicum